2014
DOI: 10.1007/s00439-014-1460-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of 60 known causative genes in 157 families with retinitis pigmentosa based on exome sequencing

Abstract: Retinitis pigmentosa (RP) is the most common and highly heterogeneous form of hereditary retinal degeneration. This study was to identify mutations in the 60 genes that were known to be associated with RP in 157 unrelated Chinese families with RP. Genomic DNA from probands was initially analyzed by whole exome sequencing. Sanger sequencing was used to confirm potential candidate variants affecting the encoded residues in the 60 genes, including heterozygous variants from genes that are related to autosomal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
104
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 67 publications
10
104
2
Order By: Relevance
“…Previous studies have shown the effectiveness of exome sequencing and targeted gene panels in determining the molecular etiology of retinal dystrophies. 7-10 Here we demonstrate its high diagnostic yield, feasibility and acceptability of exome sequencing for retinal dystrophy patients enrolled in a clinical setting.…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have shown the effectiveness of exome sequencing and targeted gene panels in determining the molecular etiology of retinal dystrophies. 7-10 Here we demonstrate its high diagnostic yield, feasibility and acceptability of exome sequencing for retinal dystrophy patients enrolled in a clinical setting.…”
Section: Introductionmentioning
confidence: 82%
“…2,3 Sixty RP causative gene mutations were found. 4 EYS is an important and common cause of RP in the Japanese, Spanish, British, Chinese, Israelis, and Palestinians. [5][6][7][8][9] Furthermore, a report has described that EYS-associated RP patients share a relatively uniform phenotype with near-normal central visual function up to their 20s.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Among these identified IRD genes, the top leading ones include USH2A, EYS, ABCA4, PDE6B, RPGR, and RHO. [7][8][9][10][11][12][13] However, a definitive molecular diagnosis of IRD remains extremely complex and challenging because mutations are only detected in 40% to 60% of cases. 4,8,[14][15][16] Most of the previous studies of IRDs have focused on single-base substitution mutations or small insertions/deletions; however, it is reasonable to speculate that large duplications or deletions can also contribute to IRDs.…”
mentioning
confidence: 99%